Recognition as an unworthy heir in court: a comparative analysis of the legislation of the Republic of Kazakhstan and Ukraine - Maksatov, N.R.; Tokarchuk, L.M. (Bulletin of the Karaganda University “Law Series”, 2024)
The purpose of this article is to analyze the institution of unworthy heirs in the Republic of Kazakhstan and Ukraine. The authors explore the theoretical and practical problems associated with its enforcement in judi-cial practice, as well as conduct a comparative legal analysis between these countries. The issues related to inheritance are analyzed, and scientifically based ways of improving this legal institution are proposed. The paper analyzes the application and implementation of the grounds for recognizing heirs as unworthy in the studied countries. The institution of unworthy heirs exists in various legal systems, and has been subject to changes throughout history. An analysis of Kazakh and Ukrainian inheritance legislation shows that some provisions on this institution do not correspond to modern ideas of justice, while others are not legally accu-rate, which makes it difficult for judicial practice to protect citizens of their violated rights. Judicial practice is also being considered on the claims of persons interested in recognizing the subjects of inheritance as unwor-thy heirs, especially those who evade the duties of maintaining the testator. The main purpose of the study is an extensive study of problematic issues of the theory and practice of the institute of unworthy heirs in these countries, taking into account existing legislation and judicial practice, as well as the proposal of ways to solve them. This work is aimed at introducing novelty and value into the scientific study of this topic.